The Zahiri school of thought in Andalusia - م.م. حيدر ناظم مايوس; م.د. حميد رضا مطهري; أ.م.د. رضا هادي الشمري (Journal of College of Education, 2024)
In this research, we dealt with the study of (the Zahiri school of thought in Andalusia), which is one of the important topics that deals with the history of some of the Islamic sects that entered Andalusia, especially at the beginning of Islamic rule in Spain. In it, I referred to the life of the founder of the Zahiri school of thought, how the school entered, and what were the factors that helped in its spread and the most important factors. The personalities who contributed to spreading the doctrine in Andalusia and then explained the reasons that led to the end of the doctrine. The reasons varied between religious and social, and thus led to people’s reluctance to adopt the Zahiri doctrine as their doctrine